Communication, theory of change, and clean energy - Cox, Robert (Frontiers in Communication, 2024)
Some years ago, I stepped away from my faculty position at the University of North Carolina at Chapel Hill (UNC) to become more deeply engaged with the Sierra Club, one of the oldest environmental NGOs in the United States. Given my research, I knew insights into strategic communication in advocacy campaigns would likely be applicable, particularly, to the climate change efforts in which I was planning to participate.Climate change campaigns, like campaigns focused on other issues, usually involve multiple forms of communication-grassroots organizing, social media, demonstrations, media coverage, placards, canvassing, etc. Beyond these tactical uses, NGOs also may conceive a strategic rationale for a campaign itself as derived from core communication principles. As it turned out, I would have an opportunity to help to design one such campaign, a messagedriven initiative to accelerate the movement toward a greater commitment to use 100% clean, renewable energy in the United States.